The Signaling Effects of the US Food and Drug Administration Fast‐Track Designation. (26th May 2016) - Miller, Kathleen L.; Nardinelli, Clark; Pink, George; Reiter, Kristin
Abstract : Pharmaceutical firms are reluctant to disclose proprietary information about a drug's likelihood of approval by the U.S. Food and Drug Administration (FDA) for fear of losing their competitive advantage. Instead, firms may use signals, like the FDA fast‐track designation, to indicate to investors the likelihood of a drug's approval. This analysis uses an event study methodology, with stock and market data from the Center for Research in Security Prices. The results show that the fast‐track designation is a strong, positive signal to investors (1998–2015), but its strength has markedly decreased over time. Results also show that the signal is strongest for the smallest firms. Copyright © 2016 John Wiley & Sons, Ltd.